Tinjauan potensi aktivitas ramuan herba sambiloto, herba meniran, dan daun kumis kucing dalam penanganan diabetik neuropati: Narative Review - Anita Purnama Sari; Elza Sundhani; Retno Wahyuningrum (Journal of Pharmaceutical and Sciences, 2026)
Diabetic neuropathy is one of the most common microvascular complications among patients with diabetes mellitus, characterized by damage to peripheral nerves due to persistently high blood sugar levels, excessive oxidation and inflammation. Conventional treatments are often not effective enough in comprehensively addressing this problem, so strategies using medicinal plants are emerging as promising options. This study aims to review the potential pharmacological activities of three medicinal plants, namely sambiloto (Andrographis paniculata), meniran (Phyllanthus niruri), and cat's whisker (Orthosiphon aristatus), in the treatment of diabetic neuropathy. This study was conducted using the Narrative Review method with a literature search of two databases PubMed and ScienceDirect with an interval of publication years 2016-2026. A total of 16 articles were selected. The three types of plants showed significant pharmacological properties, including as antioxidants, anti-inflammatory, hypoglycemic, and neuroprotective. Sambiloto functions through andrographolide compounds that inhibit the NF-κB pathway and increase Nrf2 antioxidant activity. Meniran has an effect in lowering blood glucose levels and increasing the performance of antioxidant enzymes. Cat whisker plays a role in glucose control, kidney care, and inflammation in the system.  The results of this study are expected to provide an overview of additional therapies in overcoming diabetic neuropathy through the workings of Sambiloto, meniran, and cat's whiskers have complementary potential. The combination of these three plants offers a diverse approach, but further research is needed to assess synergistic effects, safety, and the most appropriate formulation as a modern herbal treatment.